Klara Teu Nahak Pengaruh Pemahaman Sanitasi Higiene dan Keselamatan Kerja Terhadap Pelaksanaan Praktikum pastry and Bakery Di Sekolah Menengah Kejuruan Negeri 2 Godean Tahun Pelajaran 2021/2022: Pemahaman Sanitasi Higiene, Keselamatan Kerja, Pelaksanaan Praktikum - Nahak, Klara Teu (Universitas Sarjanawiyata Tamansiswa, 2025)
The purpose of the study was to determine: (1) Understanding of sanitary hygiene and work safety, (2) Understanding of the implementation of pastry and bakery practicum, (3) The effect of understanding sanitation hygiene and work safety on the implementation of pastry and bakery practicum. This type of quantitative descriptive research. The research population was 144 students. The sampling technique used simple random sampling technique with the slovin formula of 59 students. Data analysis techniques used descriptive quantitative and hypothesis testing using product moment correlation preceded by prerequisite analysis tests including normality tests and linearity tests. The results showed: (1) Understanding of sanitation hygiene and work safety was in the sufficient category (40.68%), (2) Implementation of pastry and bakery practicum was in the sufficient category (42.37%), (3) There was a positive and significant influence on understanding hygiene sanitation and occupational safety on the implementation of pastry and bakery practicum as indicated by the value of r count = 0.411 > rtable = 0.252 and the coefficient of determination (R2) is 0.169 or (16.9%).